Pengaruh Pemberian Ekstrak Rimpang Kunyit (Curcuma longa L.) terhadap Histologi Hepar Tikus Pasca Diinduksi Thioacetamide (TAA) - Eva Tyas Utami; Dewi Syaibatul Aqlina; Susantin Fajariyah; Mahriani Mahriani (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Turmeric (Curcuma longa L.) rhizome contains antioxidant compounds that can prevent damage to the liver. Thioacetamide (TAA) is an organosulfur compound in the form of crystals and is widely used as a fungicide and organic solvent in the textile, leather and paper industries, as well as being used as a motor fuel stabilizer. Continuous exposure to TAA compounds can cause hepatocyte damage in the form of parenchymatous degeneration and necrosis. The purpose of this study was to determine the effect of turmeric (Curcuma longa L.) rhizome extract on the histological appearance of the rat (Rattus norvegicus) liver after being induced by TAA. This study used a completely randomized design (CRD) with 24 Wistar rats (Rattus norvegicus) which were divided into 4 groups, namely: K- (no treatment), K+ (TAA induced 200 mg/kg BW), D1 (TAA induced 200 mg/kg BW + administration of turmeric rhizome extract at a dose of 200 mg/kg BW), and D2 (TAA induction of 200 mg/kg BW + turmeric rhizome extract at a dose of 400 mg/kg BW). TAA induction was carried out intraperitoneally, while administration of turmeric rhizome extract was carried out by gavage. Preparation of liver histology preparations using the paraffin method and Hematoxylin Eosin (HE) staining to see liver damage including parenchymatous degeneration and necrosis. The results showed that administration of turmeric rhizome extract doses of 200 mg/kg BW and 400 mg/kg BW had a significant effect on decreasing the average number of hepatocytes undergoing parenchymatous degeneration and necrosis after being induced by TAA at a dose of 200 mg/kg BW.